2019
DOI: 10.4293/jsls.2019.00016
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Routine Ambulatory Laparoscopic Cholecystectomy in Brazil

Abstract: Background and Objectives: In several developed countries, most laparoscopic cholecystectomies (LCs) are performed as an ambulatory operation (ALC) with a high rate of success. In Latin America, the experience with this procedure is still limited. Our objective is to evaluate the feasibility to implement ALC in a Brazilian teaching hospital. Methods: Data obtained from electronic medical records and study protocols of all patients who underwent an LC between January 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
5
0
4
Order By: Relevance
“…Similar to other studies, the main cause of BDI in our series was cholecystectomy. Although the risk of BDI is low in a patient undergoing cholecystectomy, in general this operation is the main cause of BDI, as cholecystectomy is the most commonly performed abdominal operation worldwide 5 . Most studies, including ours, show that the rate of BDI is higher in females, as cholecystectomy is performed three to four times more commonly in this gender due to the higher prevalence of gallstones in females 5 , 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar to other studies, the main cause of BDI in our series was cholecystectomy. Although the risk of BDI is low in a patient undergoing cholecystectomy, in general this operation is the main cause of BDI, as cholecystectomy is the most commonly performed abdominal operation worldwide 5 . Most studies, including ours, show that the rate of BDI is higher in females, as cholecystectomy is performed three to four times more commonly in this gender due to the higher prevalence of gallstones in females 5 , 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Although cholecystectomy is by far the leading cause of iatrogenic bile duct injury, other important causes are reported, including upper abdominal operations and percutaneous or endoscopic procedures. Cholecystectomy is the most common intra-abdominal surgical procedure worldwide, with an estimated incidence of bile duct injury (BDI) between 0.3-0.6% [4][5][6][7] . When the injury progresses to biliary stricture, it results in chronic exposure of the canalicular membrane to hepatotoxic bile acids.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the most unplanned readmission happened during the first seven days after discharge. Like opening cholecystectomy, ambulatory LC carries some postoperative complications as well, including wound pain, wound infection, vomiting, nausea, and urinary retention, at the early stage after surgery [ 21 ]. Rosero and Joshi [ 14 ] reported that 64.4% patients receiving ambulatory LC had unplanned readmission records in the first seven days after discharge, and 11.1% were readmitted in the first 24 hours after discharge.…”
Section: Discussionmentioning
confidence: 99%
“…Semelhante a outros estudos, a principal causa de LDB em nossa série foi a colecistectomia. Embora o risco de LDB seja baixo em um paciente submetido à colecistectomia, em geral essa operação é a principal causa de LDB, pois a colecistectomia é a operação abdominal mais realizada em todo o mundo 5 . A maioria dos estudos, incluindo o nosso, mostra que a taxa de LDB é maior no gênero feminino, pois a colecistectomia é realizada 3 a 4 vezes mais comumente nesse gênero devido à maior prevalência de cálculos biliares no gênero feminino 5,13 .…”
Section: R E S U M O R E S U M Ounclassified
“…Embora a colecistectomia seja de longe a principal causa de lesão iatrogênica do ducto biliar, outras causas importantes são relatadas, incluindo operações abdominais superiores e procedimentos percutâneos ou endoscópicos. A colecistectomia é o procedimento cirúrgico intra-abdominal mais comum em todo o mundo, com incidência estimada de lesão do ducto biliar (LDB) entre 0,3-0,6% [4][5][6][7] . Quando a lesão evolui com estenose biliar, resulta em exposição crônica da membrana canalicular aos ácidos biliares hepatóxicos.…”
Section: Introductionunclassified